2011
DOI: 10.1186/1756-6614-4-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and mood disorders: integrating novel insights from brain imaging techniques

Abstract: Thyroid hormones play a critical role in brain development but also in the adult human brain by modulating metabolic activity. Hypothyroid states are associated with both functional and structural brain alterations also seen in patients with major depression. Recent animal experimental and preclinical data indicate subtle changes in myelination, microvascular density, local neurogenesis, and functional networks. The translational validity of such studies is obviously limited. Clinical evidence for neurobiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 83 publications
(101 reference statements)
1
29
0
Order By: Relevance
“…However, it is important to note that these were onetailed, as they were calculated post hoc and we knew the direction of the results (decrease in volume). Findings from previous studies, however, would support a directional hypothesis (14)(15)(16)25).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, it is important to note that these were onetailed, as they were calculated post hoc and we knew the direction of the results (decrease in volume). Findings from previous studies, however, would support a directional hypothesis (14)(15)(16)25).…”
Section: Discussionmentioning
confidence: 44%
“…This suggests that the point at which thyroid hormone abnormalities begin during development and across the lifespan may have a greater impact on one region compared with another (13)(14)(15). Studies in neonatal, perinatal, postnatal, and adult rats have reported neuronal alterations that have been attributed to hypothyroidism, including changes in brain structure and function, short-and long-term memory, gene expression, cell signaling, and migration (9,11,12,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 97%
“…Those tracers bind to molecular structures like transporters and receptors in the human brain. Measuring of the local distribution of the bound tracers allows an estimation of regional brain activation or availability of receptors (3).…”
Section: Role Of Brain Imagingmentioning
confidence: 99%
“…Hypothyroid states are associated with both functional and structural brain alterations and also seen in patients with major depression (3). Taken together overt 0.4% and subclinical 9%, hypothyroisism is prevalent in about 9.4 % of the adult population (4) and commonly affects brain function.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Furthermore, studies involving recent brain imaging techniques provide insights into the association of the various neurologic and neurobehavioral symptoms with hypothyroidism. [8,9] There has been a characteristic association between thyroid diseases and otological symptoms. Role of certain mucopolysaccharides have been found in otitis media and also in sensorineural hearing loss.…”
Section: Introductionmentioning
confidence: 99%